Expression and characterization of Trichoderma reesei endoglucanase II in Pichia pastoris under the regulation of the GAP promoter - Kezia Abib Yerah Tjandra; Kartika Sari Dewi; Asrul Muhamad Fuad; Trisanti Anindyawati (Universitas Gadjah Mada, 2020)
Trichoderma reesei is known to be one of the organisms capable for producing various types of cellulase in high concentrations. Among these cellulases, the highest catalytic efficiency of endoglucanases II (EGII, EC 3.2.1.4) are considered important for industrial application. The characterization of the EGII is necessary since it is widely used in high-temperature reactions in the industries. In this study, the recombinant EGII protein was expressed in Pichia pastoris and it has a molecular mass of approximately 52 kDa. Recombinant EGII was purified using Ni-NTA affinity chromatography and characterized by SDS-PAGE and western blot analyses. The enzyme activity of recombinant EGII was measured using the Nelson Somogyi method to determine its optimum pH and temperature. The result showed that the maximum EGII expression was achieved after 72 h of culture incubation. The crude enzyme has optimum activity at pH 5.0, resulting in 16.3 U/mL and 14.6 U/mL activity at 40 °C and 50 °C, respectively. While the purified enzyme gave the specific activity of 115.7 U/mg under the optimum condition. Finally, our study demonstrated that recombinant EGII could retain the endoglucanase activity for 89% and 80% at 40 °C and 50 °C, respectively.